Social enterprise : cases and analysis for understanding social business - Harper, Malcolm, 1935-; Parekh, Nadiya, 1984- (Routledge, 2022)
"This book introduces students and others to the discipline of social entrepreneurship, which encourages the creation of enterprises that are socially inclusive yet economically and ecologically sustainable. In each chapter there is a useful mix of case studies about internationally well-known enterprises and other more local enterprises which are totally new. The book leads its readers to understand and appreciate entrepreneurial issues and to engage themselves in community-based activities. Social Enterprise helps readers to: analyze and articulate the blend of social, environmental and economic values which is present in all kinds of enterprise understand the issues involved in translating good intentions with multiple goals into focused, sustainable and practical actions propose alternative social enterprise management strategies based on their own analysis of case studies of entrepreneurial endeavors that are perceived to be 'social' The authors take a pragmatic yet critical approach, and this book should be core or recommended reading for Social Entrepreneurship and Social Enterprise modules at advanced undergraduate, postgraduate and MBA level"- Resumé vydavatel
Keywords: sociální podniky; udržitelný rozvoj; strategický management; social enterprises; sustainable development; strategic planning; elektronické knihy; monografie; electronic books; monographs